Cold War Liberation The Soviet Union and the Collapse of the Portuguese Empire in Africa, 1961-1975 - Telepneva, Natalia (New Cold War history., 2021)
"Cold War Liberation examines the African revolutionaries who led armed struggles in three Portuguese colonies-Angola, Mozambique, and Guinea-Bissau-and their liaisons in Moscow, Prague, East Berlin, and Sofia. By reconstructing a multidimensional story that focuses on both the impact of the Soviet Union on the end of the Portuguese Empire in Africa and the effect of the anticolonial struggles on the Soviet Union, Natalia Telepneva bridges the gap between the narratives of individual anticolonial movements and those of superpower rivalry in sub-Saharan Africa during the Cold War"--